1.4 GHz femtosecond comb generation by Fabry‐Pérot filtering of optical parametric oscillator frequency comb. Issue 13 (1st June 2013) - Ferreiro, T.I.; Lamour, T.P.; Sun, J.; Reid, D.T.
Abstract : Laser frequency combs based on optical parametric oscillators provide widely tunable sources of regularly spaced frequencies from the visible to the mid‐infrared, with potential applications in precision metrology, spectroscopy and astronomy. Reported is the extension of the comb mode spacing into the GHz domain by using a Fabry‐Pérot cavity, the length of which was electronically stabilised to a harmonic of the original pulse repetition frequency via a dither‐locking technique. A 1500 nm femtosecond optical parametric oscillator frequency comb, the repetition frequency and carrier‐envelope offset frequency of which were locked to 280 MHz and 10 MHz, respectively, was filtered by a high‐finesse cavity to generate a pulse sequence at 1.4 GHz, corresponding to a factor of five increase in the mode spacing of the comb.